Postoperative Venous Thromboembolism Outcomes Measure: Analytic Exploration of Potential Misclassification of Hospital Quality Due to Surveillance Bias. Issue 3 (March 2015) - Chung, Jeanette W.; Ju, Mila H.; Kinnier, Christine V.; Sohn, Min-Woong; Bilimoria, Karl Y.
Abstract : The Agency for Healthcare Research and Quality Patient Safety Indicator 12 Postoperative Venous Thromboembolism (VTE) does not accurately reflect true hospital quality because (1) current measure specifications preclude excluding nonclinically significant VTE from the measure numerator, and (2) not all patients in the measure denominator are at risk of VTE diagnosis.